Selective leaching of nickel from prereduced limonitic laterite under moderate HPAL conditions- part I: Dissolution - Chang Y.; Zhao K.; Pešić B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
High pressure acid leaching (HPAL) is the primary method for extraction of nickel from limonitic laterite. The severe operating conditions, the complexity of facilities, and several technical problems, such as scale formation, have always accompanied the HPAL, however. In this paper, the selective acid leaching of nickel from the pre-reduced limonitic laterite under moderate HPAL conditions was studied. For the calcine with reduction degree of 93.4%, about 88.2% nickel could be selectively extracted at 100°C with an acid/ore ratio of 0.164, leaving less then 5.0g/L iron in the solution. Further increase of leaching temperature, and the ensuing dehydration, transformed goethite in the leaching residue to hematite. When the temperatures were as high as 180°C, the recovery of nickel increased to 95.2%, within one hour, depressing the residual soluble iron to below 1.0g/L (pO2= 1.0 MPa, acid/ore= 0.287).